Innovative approaches to improving the barrier properties of natural sausage casings - I. Simonova; U. Drachuk; B. Halukh; I. Basarab; H. Koval; Y. Nutskovskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології)
This article explores the potential to enhance the quality of natural sausage casings through treatment with aqueous extracts derived from plant materials, specifically oak bark, cinquefoil roots, and common tormentil roots. Natural casings are essential in sausage production, providing a protective barrier against external factors, maintaining the shape of the product, and contributing to its long-term preservation. Due to their importance, improving the functional properties of natural casings is a priority in the food industry, particularly for ensuring product safety and extending shelf life. The primary goal of this study is to investigate how these plant-based extracts, applied at various concentrations (5:100; 10:100; 15:100), affect the fat permeability, vapor permeability, and water permeability of pork intestines used as natural casings. These properties are crucial for the casings' overall barrier performance, which directly influences the quality and shelf life of the final product. The experimental results demonstrated that using the proposed extracts improves the structural integrity of the casings by enhancing the collagen matrix, thereby positively influencing their permeability characteristics. Specifically, the study found that the highest fat permeability was achieved with the tormentil root extract at a concentration of 10:100, which resulted in a 48.43 % increase. A comparable result was observed with oak bark extract at the same concentration, showing a 45.81% increase in fat permeability. In terms of vapor permeability, the study showed that the highest values were recorded when treating the casings with cinquefoil root extract at a concentration of 10:100, leading to an increase of 0.74 %. Furthermore, all the plant-based extracts had a beneficial effect on water permeability, reducing it across the board. This reduction in water permeability suggests an enhancement of the casings' barrier properties, making them more effective in preventing moisture loss and fat leakage during the production and storage processes. In conclusion, the use of aqueous plant extracts, particularly from oak bark, cinquefoil, and tormentil, represents a promising approach to improving the functional properties of natural sausage casings. These extracts not only strengthen the collagen structure but also enhance the casings' fat, vapor, and water permeability properties, making them more resilient and better suited for modern food production needs.